2006
DOI: 10.1097/01.qai.0000219771.97303.0a
|View full text |Cite
|
Sign up to set email alerts
|

A 2-Arm, Randomized, Controlled Trial of a Motivational Interviewing-Based Intervention to Improve Adherence to Antiretroviral Therapy (ART) Among Patients Failing or Initiating ART

Abstract: Although not definitive, this study provides some evidence that MI offers an effective approach to improving adherence. Future studies able to build MI into the intervention for longer than 3 months may have a greater impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
1
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 57 publications
4
101
1
9
Order By: Relevance
“…This approach may facilitate the implementation and sustainability of this intervention in real world settings. The possibility that some patients may be more open to discussing their [46][47][48] Our randomized trial study had several strengths, including a large cohort of minority subjects across several states and the use of both an objective as well as self-reported measure of medication adherence. While many of our patients had low incomes and educational attainment, they were all insured.…”
Section: Discussionmentioning
confidence: 99%
“…This approach may facilitate the implementation and sustainability of this intervention in real world settings. The possibility that some patients may be more open to discussing their [46][47][48] Our randomized trial study had several strengths, including a large cohort of minority subjects across several states and the use of both an objective as well as self-reported measure of medication adherence. While many of our patients had low incomes and educational attainment, they were all insured.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that used master level educators, psychologists or pharmacists did not show a significant MI effect. 17,22,24,25 Duration of MI exposure did not impact adherence. Using generalized least square regression, the exponentiated betacoefficient of change by tertiles of MI exposure was 0.90 (95 % CI 0.77-1.27; p = 0.93).…”
Section: Parsonsmentioning
confidence: 99%
“…Loss to follow-up in any arm ranged from 1 % to 33 % (Table 1) with seven studies surpassing 20 %. 16,17,18,20,22,24,25 One study did not report loss to follow-up by study arm, 21 one had differential loss, 16 and three did not comment on differences in baseline characteristics by study completion status. 16,17,21 Thirteen reported no differences in characteristics by completion status, and one reported that subjects lost to follow-up in the MI group had a trend toward more depressive symptoms.…”
Section: Quality Of the Studies And Evaluation Of Biasmentioning
confidence: 99%
See 2 more Smart Citations